Hydro-chemo-mechanical coupling in sediments: Localized mineral dissolution. (September 2016) - Cha, Minsu; Santamarina, J. Carlos
Abstract: Mineral dissolution is inherently a chemo-hydro-mechanical coupled process. Field evidence and laboratory results show that dissolution may localize and form open conduits in cohesive media such as carbonate rocks. This study focuses on the evolution of localized dissolution in soils (i.e., frictional and non-cohesive granular materials) under effective confining stresses. Experimental results show the development of localized dissolution ("pipe") when a carbonate-quartz sand is subjected to reactive fluid flow: only loosely packed quartz grains remain within pipes, and the number of pipes decreases away from the inlet port. Concurrent shear wave velocity measurements show a decrease in stiffness during dissolution due to stress and fabric changes, and more complex signal codas anticipate the development of internal heterogeneity. The discrete element method is used to simulate localized vertical dissolution features in granular materials, under constant vertical stress and zero lateral strain far-field boundaries. As porosity increases along dissolution pipes, vertical load is transferred to the surrounding soils and marked force chains develop. In terms of equivalent stress, principal stress rotation takes place within pipes and the sediment reaches the Coulomb failure condition inside pipes and in the surrounding medium. Dissolution pipes alter the geo-plumbing of the subsurface, enhance fluid transport but limit the long term performance of storage systems, alter the fluid pressure and effective stress fields, soften the sediment and may trigger shear failures. Highlights: The paper studies localized dissolution in noncohesive soils under effective stress. Sediments become more compressible after localized dissolution. The porosity increases within pipes, filled with loose non-soluble quartz. Shear wave velocity decreases, and codas indicate increased spatial variability. Principal stress rotates in pipes, and sediment reaches Coulomb failure condition.